1997
DOI: 10.1093/jee/90.5.1087
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Seven Monoterpenoids to Tracheal Mites (Acari: Tarsonemidae) and Their Honey Bee (Hymenoptera: Apidae) Hosts When Applied as Fumigants

Abstract: Laboratory bioassays were conducted to characterize the acute toxicity of 7 monoterpenoids to tracheal mites, Acarapis woodi (Rennie), and their honey bee, Apis mellifera L., hosts. Citral, thymol, carvacrol, a-terpineol, pulegone, d-limonene, and menthol were applied as fumigants to mite-infested honey bees. Thymol and menthol were the most toxic compounds to honey bees, and a-terpineol was the least toxic. Menthol, citral, thymol, and carvacrol were more toxic to tracheal mites than to honey bees. Pulegone, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(43 citation statements)
references
References 15 publications
1
41
0
1
Order By: Relevance
“…For example, if bees are exposed to different pyrethroid pesticides which share the same mode of action, then the observed toxicity is a sum of the doses of the different pyrethroid pesticides (e.g. tau-fluvalinate and bifenthrin, Ellis and Baxendale, 1997). Differential potencies between different agents with similar modes of action may need to be taken into account (Robertson et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…For example, if bees are exposed to different pyrethroid pesticides which share the same mode of action, then the observed toxicity is a sum of the doses of the different pyrethroid pesticides (e.g. tau-fluvalinate and bifenthrin, Ellis and Baxendale, 1997). Differential potencies between different agents with similar modes of action may need to be taken into account (Robertson et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Although the experience has shown remarkable in vitro toxicity against Varroa mites, further studies should be conducted in the field to assess possible effects on brood, queen mortality and possible interference in beneficial microflora within the internal environment of the colony, since monoterpenoids such as Thymol may not be safe for honey bee colonies. These compounds play a role as broad spectrum pesticides (Isman, 2006) and in previous studies, Thymol and menthol had been found to be among the most toxic of all terpenoids tested when applied to honey bees as a fumigant (Ellis & Baxendale, 1997). Despite being naturally derived, Thymol treatment can induce brood removal (Marchetti, Barbattini & D'Agaru, 1984;Floris et al, 2004) and result in increased queen mortality in field conditions (Whittington et al, 2000).…”
Section: Toxicity Of the Binary Mixture On Apis Mellifera And Varroa mentioning
confidence: 99%
“…Menthol was found to be about 19 times more toxic to mites than to bees. Menthol can be used in the control of these mites and is commercially available (Ellis and Baxendale, 1997). Calderone and Spivak, (1995) studied thymol, eucalyptus oil, and menthol and camphor mixture.…”
Section: Essential Oils Against Honey Bee Mitesmentioning
confidence: 99%
“…They are important for plant defense as possessing antimicrobial, antiparasitic, antiviral, antifungal properties (Hyldgaard et al, 2012). Some plant essential oils or components have a broad spectrum of activity against pathogenic bacteria and fungi (Kotan et al, 2008); tick infestation (Coskun et al, 2008); human lice and house dust mite (Williamson et al, 2007); insect vector (Chaiyasit et al, 2006); honey bee mites (Calderone et al, 1997;Ellis and Baxendale, 1997). Also, essential oils obtained by steam distillation of plant leaves and leaves of some aromatic plants (especially in Myrtaceae and Lamiaceae families, but also other plant families) are used to protect traditionally stored grain and legumes, and to repel flying insects in the house (Isman, 2000).…”
Section: Introductionmentioning
confidence: 99%